Determinants of Household Intention to Reduce Food Waste in the Jabodetabek Region - Lina Salim; Veronika Yulia (Integrated Journal of Business and Economics (IJBE), 2025)
This study investigates the effects of Environmental Awareness, Social Media Usage, Economic Concern, and Impulsive Buying on household Intention to Reduce Food Waste within the Jabodetabek region. Employing a purposive non-probability sampling technique, data were collected through an online survey involving 280 female respondents responsible for food preparation at home. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to test nine hypotheses. The results indicate that four hypotheses were supported, while five were not. Specifically, Environmental Awareness, Social Media Usage, and Attitude toward Food Waste exhibited significant positive effects on the Intention to Reduce Food Waste. Conversely, Economic Concern and Impulsive Buying showed no direct impact on the intention to reduce waste. These outcomes highlight the importance of psychological and informational factors over purely economic considerations in shaping pro environmental household behavior. The findings offer valuable insights for policymakers and practitioners, particularly marketers, in formulating effective strategies to minimize food waste. Recommended actions include designing targeted communication and advertising campaigns, establishing supportive policies to reduce household food waste, and developing educational initiatives to foster sustainable consumption habits. Overall, the study contributes to understanding behavioral determinants of food waste reduction in urban household contexts and underscores the role of awareness and digital engagement in promoting sustainable food management practices. The study also highlights the unique role of women managing household food preparation, offering gender-based insight into sustainable consumption behavior in Indonesia.